Reduced Cyclic Adenosine Monophosphate Level in Hippocampal CA1 Participates in Propofol Induced Amnesia in Rats - Li, Weiwei; Yu, Lingling; Yan, Xiaodi; Cai, Linlin; Wan, Li; Teng, Qinyu; Li, Yonghua; Wang, Yun; Xu, Haitao (Frontiers in Neuroscience, 2018)
Propofol inhibits long-term potentiation（LTP）in the hippocampal CA1 region and impedes episodic memory formation. However, the molecular mechanisms involved in the effect of propofol are still poorly understood. It had been reported that propofol inhibited cAMP response element binding protein signaling, which was proposed to contribute to memory retention impairment in rats. Here, we first demonstrated that propofol perfusion could inhibit forskolin induced LTP in the rat hippocampal CA1 slices. Propofol also reduced the level of cAMP, which could be reversed by non-selective PDE inhibitor IBMX. We further discovered that propofol could increase both PDE4 activity and PDE4AX protein expressions in the hippocampal CA1 region. Furthermore, pretreatment of rolipram, a PDE4 inhibitor, rescued propofol induced inhibition of CA1 LTP and the impairment of hippocampus-dependent memory formation in rats. Thus, our results suggest that reduced levels of cAMP by increasing PDE4 activity and PDE4AX protein expressions in the hippocampal CA1 region plays an important role in the propofol-induced amnesia.